P2.23 Hepatotoxicity and anaemia co-morbidity in treated aids patients in fundong sub division in the northwest region of cameroon. (8th July 2017) - Abongwa, Lem Edith; Nyamache, Anthony Kebira; Akono, Nantia; Sunjo, Stanley; Balan, Vera Nange, Hebert; Charles, Fokunang; Okemo, Paul; Torimiro, Judith
Abstract : Introduction: Hepatotoxicity and anaemia are relevant adverse effects of ART and can cause interruption of therapy and death. However, there is dearth of information on hepatotoxicity and anaemia co-morbidity especially in rural areas. The aim of the study was to identify the prevalence of Hepatotoxicity and Anaemia co-morbidity among HIV treated patients. Methods: A total of 150 drug naïve patients visiting the day hospital in Fundong District Hospital were recruited into the study from January-March 2015 and follow up for 18 months. Baseline and 18 months levels of CD4 counts, alanine transaminase(ALT), and aspartate transaminase(AST) and Haemoglobin concentration(Hb) were determined. HIV was diagnosed using Alere determine HIV rapid test kit and Bioline or Oral Quick test kit for the confirmatory test. CD4 counts were determined using the Alere Pima CD4 cartridge machine. Hb, ALT and AST counts were determined by colometric enzymatic reaction using the urit 3300 machine and classified based on age and sex. Results: The majority of patients were female 115 (76.7%) and belonged to the <30 years age range 48 (32%). The prevalence of anaemia decreased from 86 (57.3%) to 69 (45.6%) at the end of the study period. In all 46 (30.7%) patients had hepatotoxicity and anaemia co-morbidity which was higher in the age group <30 years 30 (41.7%) and in female 37 (32.2%). A total of 1 (0.7%) and 10 (6.7%) patients develop severe hepatotoxicity using ALT and AST respectively. The prevalence of hepatotoxicity was higher in male (31.4% and 62.9%) and in the age group 30–39 years (29.5% and 68.2%) for ALT and AST, respectively. The prevalence of anaemia and elevated AST and ALT were higher in persons with CD4 <200 cells/µl. There was a significant correlation between CD4 and Hb (r=0.193), CD4 and ALT(r=−0.149) and CD4 and AST(r=−0.193). Conclusion: Hepatotoxicity especially Grades 1–2 and not anaemia is a significant adverse effect of ART upon time.